Design of a blow off valve for turbocharged engine applications - Mohd Fadhli, Mohd Nasir (2007)
On a turbo engine, the Blow of Valve (BOV) is used to relieve the pressure from the turbo output when the throttle is closed. Without the BO y, when the throttle is closed the turbo is suddenly trying to pump air against a closed throttle plate. This creates pressure spike in the turbo output hose and will send back the pressure to the turbine and can damage the turbo engine. When the throttle is opened again, the turbo has to spin up again, creating turbo lag. So, the present of the BOY will opened when the throttle is closed and pressurized the pressure spike to the air to avoid those phenomena. So, good flow of the air inside the BOV is important, the air will smoothly pressurized to the atmosphere if there is no back pressure inside the system. Computer aided design (CAD) and computational fluid dynamic (CFD) software were used as a tool for the design. This design is the improvement of the aftermarket design. The piston surface, size of vent, inlet ports, outlet ports, and also spring plays the role in the BOy. The design analyzed using CFD so can see the flow trajectories of the air inside the BOy.